EVALUASI PROGRAM DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KOTA PEKANBARU TERHADAP TINDAK KEKERASAN PEREMPUAN DAN ANAK TAHUN 2018-2019 - Wahyuni Permata Sari Br Bangun; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Pekanbaru City is in the first rank of cases of violence against women and children in Riau Province with a total of 418 cases. There was an increase in the number of cases and the peak was in 2018-2019 with 222 reports. This research problem is how the program evaluation is carried out by the Department of Women's Empowerment and Child Protection in Pekanbaru City against violence against women and children in 2018-2019 and the implementation of programs carried out by the Pekanbaru City Women's Empowerment and Child Protection Agency against violence against women and children in 2018-2019. This study aims to describe the evaluation of programs carried out by the Pekanbaru City Women's Empowerment and Child Protection Agency against violence of women and children in 2018-2019 and the obstacles to program implementation carried out by the Department of Women's Empowerment and Child Protection in Pekanbaru City against violence against women and children. 2018-2019 This research is a type of descriptive research using a qualitative approach. Data collection techniques in this study using interview techniques, observation and documentation, data analysis used is qualitative analysis. The location of the research was carried out at the Women Empowerment and Child Protection Office of Pekanbaru City, the Family Learning Center (PUSPAGA), the Pekanbaru City Children's Forum and the Riau Women's Children's Organization NGO (RUMPARI). The results of this study are based on the theoretical indicators used by the writer are: 1. Effectiveness, the activities carried out are not effective because the planned qualitative and quantitative objectives are not achieved. 2. Efficiency, the program implemented is not efficient. This is evidenced by the use of the budget in implementing the program but not achieving the expected goals. 3. Adequacy, unavailability of adequate facilities and infrastructure and the absence of supports systems from related agencies which are the program targets of PUSPAGA. 4. Similarity, the programs implemented are not evenly distributed among all communities. Because only a few groups of people are the program targets. 5. Responsiveness, programs implemented by the agency have not received a very good response from NGO’s. 6. Accuracy and inaccuracy in the mapping of cases carried out by the agencies. So that the programs carried out by the agency are mostly based on predictions so that the programs are often not on target. Keywords: Evaluation, Effectiveness and Efficiency, Adequacy and Similarity, Responsiveness and Accuracy, Violence